2017
DOI: 10.17221/55/2016-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary L-carnitine and fat type on the performance, milk composition and immunoglobulin in sows, and immunological variables of sows and piglets during late gestation and lactation

et al.

Abstract: Tian M., Wang N., Su G., Shi B., Shan A. (2017): Effects of dietary l-carnitine and fat type on the performance, milk composition and immunoglobulin in sows, and immunological variables of sows and piglets during late gestation and lactation. Czech J. Anim. Sci., 62,[185][186][187][188][189][190][191][192][193][194] An experiment with a 2 × 2 factorial arrangement of treatments (n = 12 sows/treatment) was conducted to investigate the effect of maternal dietary supplementation with 2 different l-carnitine level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Porcine milk composition in 2010s. References used to calculate averages of milk composition in last 10 years: Kim et al [ 104 ], Tian et al [ 105 ], Bai et al [ 106 ], Wang et al [ 107 ], Shen et al [ 108 ], Decaluwe et al [ 109 ], Wang et al [ 110 ], Samanc et al [ 111 ], Loisel et al [ 112 ], Krogh et al [ 113 ], Flummer and Theil [ 114 ], Zhao et al [ 115 ], Velayudhan and Nyachoti [ 116 ], Rosero et al [ 117 ], Farmer et al [ 118 ], Park et al [ 119 ], Wang et al [ 120 ] …”
Section: Composition Of Protein Fat and Lactose In Sow Milkmentioning
confidence: 99%
“…Porcine milk composition in 2010s. References used to calculate averages of milk composition in last 10 years: Kim et al [ 104 ], Tian et al [ 105 ], Bai et al [ 106 ], Wang et al [ 107 ], Shen et al [ 108 ], Decaluwe et al [ 109 ], Wang et al [ 110 ], Samanc et al [ 111 ], Loisel et al [ 112 ], Krogh et al [ 113 ], Flummer and Theil [ 114 ], Zhao et al [ 115 ], Velayudhan and Nyachoti [ 116 ], Rosero et al [ 117 ], Farmer et al [ 118 ], Park et al [ 119 ], Wang et al [ 120 ] …”
Section: Composition Of Protein Fat and Lactose In Sow Milkmentioning
confidence: 99%
“…This finding was in accordance with those of Mahmoud et al [31], who found that the diets supplemented with LC decrease the malondialdehyde level and increase catalase activity in hepatic tissue, breast, and thigh muscles, especially with the higher dose (600 mg/kg) in growing Japanese quail. Tian et al [45] concluded that the LC has an exogenous anti-oxidant property by preventing the formation of reactive oxygen species, scavenging free radicals, and protecting cells from peroxidative stress. The present results were similar to that demonstrated by Mohammadi et al [46] and Wang et al [47].…”
Section: Antioxidant Profilementioning
confidence: 99%
“…However, the positive effect of calf thymus extract on humoral and cellular immunity may be attributed to increasing lymphocyte cells % [49]. The effect of LC can be linked to its potential to induce immunomodulatory effects, since supplementation boosts protective immunity after vaccination by increasing neutrophil and macrophage activity [45]. Cakir and Yalcin [50] found a putative positive effect of LC on humoral immunity of broilers receiving low energy diets.…”
Section: Phagocytic Activity % and Phagocytic Indexmentioning
confidence: 99%